Research on Attitude Calculation Based on MEMS Sensor. Issue 1 (1st March 2023) - Zhang, Cheng; Lin, Guomin; Chen, Zhen
Abstract: According to the requirement of attitude measurement of moving carriers, the MPU9250 sensor is used to collect real-time data on moving carriers. However, the accuracy of the sensor is low, and there is a large error between the calculated attitude value and the real value. Therefore, in this paper, the adaptive complementary filtering algorithm and ellipse fitting method are adopted, which effectively reduces the error and makes the attitude angle more accurate. Based on the Euler angle and quaternion differential equation, the attitude angles ϕ and θ are obtained by correcting the gyroscope value according to the adaptive complementary filtering algorithm. Then the magnetometer in the MPU9250 sensor is processed by ellipse fitting based on the least square method, and the heading angle ψ of the moving carrier is calculated. Through static and dynamic experiments, it can be seen that the attitude angle obtained by adaptive complementary filtering and ellipse fitting is more accurate and stable.